EMPOWERING WOMEN IN CHILD PARENTING PATTERNS THROUGH PAAR "CINTA KASIH" EDUCATION - Sri Rejeki; Siti Hasanah; Zedi Muttaqin; Ibrahim Ibrahim; Saddam Saddam (JCES (Journal of Character Education Society), 2021)
Abstrak: Tujuan kegiatan ini adalah edukasi perempuan dalam pola asuh anak melalui edukasi paar “Cinta Kasih”. Sasaran kegiatan pengabdian ini adalah pengurus PKK Desa Juru Mapin khususnya POKJA 1, Perwakilan Pengurus Organisasi Remaja Desa Juru Mapin. Kegiatan telah melalui 3 tahapan yaitu; persiapan, pelaksanaan, dan monitoring dan evaluasi. Pelaksanaan kegiatan melalui metode ceramah dan role-playing. Kegiatan berhasil dilaksanakan, terlihat dari semangat peserta mengikuti kegiatan, semangat untuk memahami konsep Paar “Cinta Kasih”, memiliki keinginan yang kuat untuk menerapkan konsep Paar “Cinta Kasih” dengan harapan anak tumbuh kembang sesuai harapan, dan mulai berkomitmen untuk menerapkan konsep Paar “Cinta Kasih” agar terwujud keluarga yang harmonis, antara orangtua dan anak. Dari kegiatan ini juga terbentuk PIKR (Pusat Informasi dan Konseling Remaja) dan pengembangan kelompok BKR (Kelompok Bina Keluarga Remaja) di Desa Juru Mapin.Abstract: The purpose of this activity is the education of women in the parenting pattern through the education of "Cinta Kasih" paar. The target of this devotional activity is the management of PKK Juru Mapin Village, especially POKJA 1, Representative of the Youth Organization of Juru Mapin Village. The activity has gone through 3 stages, namely; preparation, implementation, and monitoring and evaluation. Implementation of activities through lecture and role-playing methods. The activity was successfully carried out, seen from the spirit of participants following the activity, the spirit to understand the concept of Paar "Cinta Kasih", have a strong desire to apply the concept of Paar "Cinta Kasih" with the hope of the child to grow up as expected, and began to commit to apply the concept of Paar "Cinta Kasih" to realize a harmonious family, between parents and children. From this activity also formed PIKR (Youth Information and Counseling Center) and the development of BKR group (Youth Family Development Group) in Juru Mapin Village.